Stitches a memoir... - Small, David 1945- (W.W. Norton & Co., 2009)
"In Stitches, Small, the award-winning children's illustrator and author, re-creates this terrifying event in a life story that might have been imagined by Kafka. As the images painfully tumble out, one by one, we gain a ringside seat at a gothic family drama where David-- a highly anxious yet supremely talented child-- all too often became the unwitting object of his parents' buried frustration and rage." -- Provided by publisher